Switching performance characterization of SiC Schottky diodes in switch-mode DC-DC converters - Libby, Rochie Ligaya S. (2004)
The trend in switch-mode converters is towards system miniaturization and an increase in power density. These goals are primarily achieved by an increase in switching frequency and converter efficiency. The Silicon Carbide (SiC) Schottky diode is a revolutionary device that exhibits no reverse recovery, fast switching, negligible temperature dependence on switching behavior and high reverse voltage capability. These characteristics make it a suitable device in applications that demand high switching frequencies and large blocking voltages such as in power factor correction circuits. Recent studies dealing with the comparison of SiC Schottky with ultra-fast diodes are application-specific and they do not quantify the contribution of the superior switching performance of the SiC Schottky to the improvement of the switch-mode converter's efficiency. This research compares the performance of the SiC Schottky diode to leading ultra-fast diodes in buck and buck-boost DC-DC switching converters and conduction losses in the buck and buck-boost converters with the input voltage, load current, switching frequency and diode turn-off dl/dt rate as the parameters. The experiments provide as assessment of the contribution of the superior switching characteristics of the SiC Schottky to the improvement of the converter efficiency.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Diodes, Schottky-barrier.; Switching power supplies; Electric current converters; DC-to-DC converters; Diodes, Switching